The Reinforcement Al Zuot Intersection Bridges Approaches in AL- Ramadi Using Geo-Textile (Journal of University of Babylon for Engineering Sciences, 2019)
One of the major problems of implementation the bridges approaches, and often may be a settlement in the soil, which requires the creation of retaining walls on both sides of the approaches that fill by compacted soil. The needed dispensed of these walls, by filled the bridge shoulders  by reinforced soil and precast concrete sheets thereby saving the cost and time of the creation of this project in high degree. Soil reinforcement be homogeneous nor showing any settlement problem in the future.Research aims to reach a scientific theory to study the behavior of the weak clay soil when reinforcing fibers and the possibility of studying the various factors that influence this behavior and the possibility of reinforcing of bridge approaches using these fibers. Due to many of the problems that appeared in the most of the facilities at the implementation, it is revealed that the soil had happened to her settlement because the bearing is not commensurate to create a work of concrete with high loads, and these problems are what we are experiencing today when creating approaches bridges and abutments wall, it has become necessary to strengthen the soil to resist any it works arise.Through these laboratory tests, which were conducted on a sample of poor soils found that fibers geotextile working to increase the shear strength of the soil in order to increase soil effective shearing strength parameters  as shown by the results of the direct shear test and this gives resistance to shearing the best of the soil due to the presence of fiber in soil.Through field tests conducted on a sample of poor soils and soil fiber geotextile a way to test by the plate load bearing. The geotextile fiber loading working to increase the tolerability by more than twice the tolerability without fiber.